2022
DOI: 10.1002/int.22775
|View full text |Cite
|
Sign up to set email alerts
|

Bin similarity‐based domain adaptation for fine‐grained image classification

Abstract: Fine‐grained classification tasks are challenging because fine‐grained data sets are quite scarce. Thus, we utilized the domain adaptation method to migrate knowledge from large, labeled data sets to fine‐grained target data sets. We employed the bin similarity (BS) algorithm to measure and select the approximate domains from large‐scale data sets to the fine‐grained target domains. Source domain feature space was divided into multiple bins and the features of the target domains were sampled to fill the bins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Image processing involves a variety of different tasks, such as image retrieval, 7,8 image registration, 9 and even video retrieval 10 . Image retrieval is one of the most essential and prevalent tasks in image processing and is one of the crucial work during constructing smart services as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Image processing involves a variety of different tasks, such as image retrieval, 7,8 image registration, 9 and even video retrieval 10 . Image retrieval is one of the most essential and prevalent tasks in image processing and is one of the crucial work during constructing smart services as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The neural networks have inherent vulnerabilities. 4,5 They can be attacked by adversarial examples. 6 On the other hand, the sensors on unmanned vehicles are too complex [7][8][9][10][11][12][13] and they can be cheated by false signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the security problems of unmanned vehicles are more and more serious since it depends on AI systems, such as neural networks and relies on too many sensors. The neural networks have inherent vulnerabilities 4,5 . They can be attacked by adversarial examples 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Deep neural networks (DNNs) have achieved superior performance in many applications. [1][2][3][4] However, recent works have shown that DNNs are vulnerable to adversarial examples, [5][6][7][8] that is, input images perturbed by imperceptible noise can lead to inaccurate predictions of DNNs. The existence of adversarial examples raises concerns in security-sensitive applications, for example, self-driving cars 9 and face recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Deep neural networks (DNNs) have achieved superior performance in many applications 1–4 . However, recent works have shown that DNNs are vulnerable to adversarial examples, 5–8 that is, input images perturbed by imperceptible noise can lead to inaccurate predictions of DNNs.…”
Section: Introductionmentioning
confidence: 99%